KONSENTRASI DAN KUALITAS PERGURUAN TINGGI SWASTA DI KOPERTIS WILAYAH XII - Radianta, Elia (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
In an effort to improve the strength of the nation to compete through higher education, this study was taken with an objective to know the concentration and quality of private universities under the Region XII Private University Coordinative Body using (1) Geographical Information System Analysis, (2) Table Analysis, and (3) Logit Model Analysis. It was found that, of the 75 private universities in the region, 48% were geographically concentrated in Papua Province, 21.33% in Maluku, 17.33% in West Papua, and 13.33% in North Maluku. It was suggested that (1) the government attention should be directed either through human resources improvement or local economic development; (2) the government commitment was needed to advocate the human resources in each region to be the future leaders in improving the quality of private universities to fulfil the expectation of HELTS; and (3) the institutional capacity improvement needed to be extended